Impact of alcohol consumption upon medical care utilization and costs in men: 4-year observation of National Health Insurance beneficiaries in Japan - Anzai, Yukiko; Kuriyama, Shinichi; Nishino, Yoshikazu; Takahashi, Kohko; Ohkubo, Takayoshi; Ohmori, Kaori; Tsubono, Yoshitaka; Tsuji, Ichiro (Addiction (Abingdon, England), 2005)
ABSTRACT Aims  The purpose of the present study was to examine the association between alcohol consumption and in‐patient and out‐patient care utilization and its costs, respectively. Design and participants  The present data were derived from a 4‐year prospective observation of National Health Insurance beneficiaries in rural Japan. A total of 17 497 men aged 40–79 years were analysed, after excluding subjects who at the baseline reported having had at least one of four chronic diseases: stroke, myocardial infarction, liver disease and cancer. Alcohol intake was classified into five groups, not including ex‐drinkers: life‐long abstainers and ethanol intakes of 1–149 g/week, 150–299 g/week, 300–449 g/week, and ≥450 g/week. Findings  The hospital days and in‐patient care cost showed a U‐shaped relationship with alcohol consumption. In‐patient cost was highest for those consuming more than 450 g/week [£74.96, 95% confidence interval (CI): 54.39, 95.52] and for life‐long abstainers (£69.16, 95% CI: 62.08, 77.83), and lowest for those consuming 150–299 g/week (£51.69, 95% CI: 45.33, 58.04). In‐patient use by age specific analysis also showed a U‐shape at all ages, and was lowest for those consuming 1–149 g/week in youngest age group. In contrast, the number of physician visits and out‐patient cost showed an inverse linear relationships with alcohol consumption. Conclusions  This study suggests that in‐patient use shows a U‐shaped curve and out‐patient use shows an inverse linear relationship to alcohol consumption.